2017
DOI: 10.1016/j.yhbeh.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal oxytocin, but not vasopressin, augments neural responses to toddlers in human fathers

Abstract: This study investigates paternal brain function with the hope of better understanding the neural basis for variation in caregiving involvement among men. The neuropeptides oxytocin (OT) and vasopressin (AVP) are implicated in paternal caregiving in humans and other species. In a double-blind, placebo-controlled, within-subject pharmaco-functional MRI experiment, we randomized 30 fathers of 1–2 year old children to receive either 24 IU intranasal OT before one scan and placebo before the other scan (n = 15) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 83 publications
6
72
3
Order By: Relevance
“…Although many factors can induce variability in the efficiency of intranasal administration in primates, including variability in the anatomy of the area, doses or source of administration (nebulisers, nasal spray, aerosolised OXT, etc. ), the evidence supports the possibility of either a direct or indirect central effect of exogenous OXT. A few studies have found evidence to support the beneficial effects of intranasal OXT in paternal behaviour and in promoting protective behaviour in mothers suffering from postpartum depression .…”
Section: Implications Of Oxytocin In Human Parental Behaviour and Moosupporting
confidence: 69%
See 1 more Smart Citation
“…Although many factors can induce variability in the efficiency of intranasal administration in primates, including variability in the anatomy of the area, doses or source of administration (nebulisers, nasal spray, aerosolised OXT, etc. ), the evidence supports the possibility of either a direct or indirect central effect of exogenous OXT. A few studies have found evidence to support the beneficial effects of intranasal OXT in paternal behaviour and in promoting protective behaviour in mothers suffering from postpartum depression .…”
Section: Implications Of Oxytocin In Human Parental Behaviour and Moosupporting
confidence: 69%
“…found that intranasal OXT decreased amygdala activation and increased activation of the insula and inferior frontal gyrus when women with insecure attachment representations heard infant cries. In addition, intranasal OXT also increased the BOLD (blood‐oxygen‐level dependent) functional MRI response in the caudate nucleus and dorsal anterior cingulate of human fathers who were viewing images of their children, suggesting that OXT enhanced the activation of brain regions involved in reward, empathy and attention . In macaques, several studies also found increased CSF OXT around 30‐40 minutes after intranasal OXT administration .…”
Section: Implications Of Oxytocin In Human Parental Behaviour and Moomentioning
confidence: 98%
“…For fathers' OT, past observational research on Israeli families showed that men with elevated OT were more affectionately and positively engaged when they interacted with their infants (Feldman et al, , ; Gordon et al, ). Among U.S. fathers, exogenous intranasal OT enhanced fathers' neural responses to photographs of their own children in brain areas relevant to reward and attention (Li, Chen, Mascaro, Haroon, & Rilling, ). In similar cultural settings, fathers receiving exogenous OT engaged in positive behaviors with their young children, such as encouragement and stimulation of exploration (Naber, van Ijzendoorn, Deschamps, van Engeland, & Bakermans‐Kranenburg, ; Weisman, Zagoory‐Sharon, & Feldman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although exogenous administration of hormones helps us better understand the causal nature of these effects, one should proceed with caution when interpreting the effects of exogenous hormones because they are dependent upon the individual's endogenous hormone levels . Furthermore, despite the novelty and originality of the studies reported in the current review, one must consider limiting factors such as sample size and individual differences within samples . Most of these empirical studies have been published in the last 10 years and require replication in larger and more generalisable cohorts.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Future research should use neuroimaging paradigms to compare whether mothers and fathers differentially process their infant's emotional cues. A few studies to date have looked at these brain responses separately in mothers and fathers . However, to our knowledge, no study has addressed the gaps in the literature by specifically comparing brain responses between mothers and fathers to their own infant's emotional cues.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%